PENGARUH PENGALAMAN KERJA, KOMPENTENSI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. TUKADMAS KOTA BIMA - WULANDARI, TRI; APRIANTI, KARTIN; HIDAYANTI, MAWAR (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This research aims to determine the influence of work experience, competence and work motivation on employee performance at PT Tukadmas Bima City partially and simultaneously. This research is associative research with a research instrument using a Likert scale. The sampling technique used was purposive sampling with the total research sample being 38 permanent employees. Data collection techniques use observation, questionnaires and literature study. The data analysis technique uses multiple linear regression. The research results show that partially only work motivation has a significant effect on employee performance at PT. Tukadmas Bima City, but simultaneously work experience, competence and work motivation have a significant effect on employee performance at PT. Tukadmas Bima City.